Rancang Bangun Sistem Informasi Kepegawaian PT Indo Global Cemerlang - Fendrius, Wilsen; Rachmadi, Muhammad (Universitas Multi Data Palembang, 2025)
PT Indo Global Cemerlang is a company engaged in the sale of spare parts,lovated in Palembang, South Sumatra, specificially at ruko 1B, Jl. H. Abdul Rozak Patal-Pusri No.2630, 2 Ilir, Kec. Ilir Tim. II, Palembang City, South Sumatra, 30163.Currently, the company still employs conventional methods for employee data management, such as physical documents, manual recording, andpaper forms. These methods result in inefficiencies in recruitment, attendance, leave management, and the handling of promotions and rewards. The Research methodology applied in developing the employee information system utilizes the RUP(Rational Unified Process) methodology. The final result of this research is a web-based employee information system designed to facilitate and streamline the company’s processes.